Ghosts at the table : riverboat gamblers, Texas rounders, Internet gamers, and the living legends who made poker what it is today /: riverboat gamblers, Texas rounders, Internet gamers, and the living legends who made poker what it is today. (2009) - Unknown
No abstract available